Using a Smart Phone as a Standalone Platform for Detection and Monitoring of Pathological Tremors - Daneault, Jean-Francois; Carignan, Benoit; Codère, Carl Éric; Sadikot, Abbas F.; Duval, Christian (Frontiers in Human Neuroscience, 2013)
INTRODUCTION: Smart phones are becoming ubiquitous and their computing capabilities are ever increasing. Consequently, more attention is geared towards their potential use in research and medical settings. For instance, their built-in hardware can provide quantitative data for different movements. Therefore, the goal of the current study was to evaluate the capabilities of a standalone smart phone platform to characterize tremor. RESULTS: Algorithms for tremor recording and online analysis can be implemented within a smart phone. The smart phone provides reliable time- and frequency-domain tremor characteristics. The smart phone can also provide medically-relevant tremor assessments. DISCUSSION: Smart phones have the potential to provide researchers and clinicians with quantitative short- and long-term tremor assessments that are currently not easily available. METHODS: A smart phone application for tremor quantification and online analysis was developed. Then, smart phone results were compared to those obtained simultaneously with a laboratory accelerometer. Finally, results from the smart phone were compared to clinical tremor assessments.